ANALISIS KONDISI SOSIAL EKONOMI MASYARAKAT TANI DI SEKITAR CV PROMINDO UTAMA (Studi Kasus di Dusun Panggang, Kecamatan Losari, Kabupaten Cirebon) - Nada Zahrotul Jannah; Yayat Sukayat (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
CV Promindo Utama is a food and beverage processing industry in Panggang and has been established for 24 years. The existence of an industry in the middle of the life of rural communities does not always only bring benefits to the socio economic community around it. The purpose of this research is to find out the socio economic condition of the Panggang community on the existence of CV Promindo Utama. The research method used a descriptive qualitative method. Data collection techniques used are interviews, observations, and documentation. Data analysis techniques used are data reduction, data presentation, and inference. The results showed that the social interaction between the people of Panggang and CV Promindo Utama has a good relationship. The existence of CV Promindo Utama helps the education of the community of Panggang by building and assisting the operation of Islamic Kindergarten. Waste from industry products produced by CV Promindo Utama is well managed. The income of the people of Panggang has not increased on the existence of CV Promindo Utama. There are no people from Panggang who work at CV Promindo Utama. The existence of CV Promindo Utama adds to the business opportunities of the local community.